1972
DOI: 10.1002/ps.2780030512
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorvos residues in food arising from the domestic use of dichlorvos PVC strips

Abstract: Trials have been carried out with “VAPONA” Pest Strips under practical conditions in houses in the U.K. and France. The purpose of these trials was to determine the residues of dichlorvos that occur in food prepared in kitchens in which strips were placed. Samples, each of which consisted of the combined food and drink for an adult for a day, were taken at intervals during the trials. The food items were exposed and the meals prepared, including any cooking, in the way normal to the household. The analyses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Elgar et al (1970) reported on a method which was developed for analysis of dichlorvos in crops and tissues with a sensitivity to 0.01 ppm. This method was used by Elgar et al (1972) for determination of dichlorvos residues in meals exposed to vapors from dichlorvos resin strips in houses in England and France. The method was found to be unsatisfactory for use with the meals exposed in this experiment because of their high fat content, which would have required a lengthy steam distillation cleanup procedure.…”
mentioning
confidence: 99%
“…Elgar et al (1970) reported on a method which was developed for analysis of dichlorvos in crops and tissues with a sensitivity to 0.01 ppm. This method was used by Elgar et al (1972) for determination of dichlorvos residues in meals exposed to vapors from dichlorvos resin strips in houses in England and France. The method was found to be unsatisfactory for use with the meals exposed in this experiment because of their high fat content, which would have required a lengthy steam distillation cleanup procedure.…”
mentioning
confidence: 99%